Doing it all as a solo parent - Dowling, Daisy; Schulte, Brigid, 1962-; Grant, Heidi; Achor, Shawn (Boston, Massachusetts : Harvard Business Review Press, 2022)
You're only one person--but you're not alone. As a single parent, you know your life is different from the other working parents around you. With the pressure to perform well at work and no partner to assist with tasks at home (let alone major crises), you likely find yourself pulled in all directions, with many responsibilities and little support. Doing It All as a Solo Parent offers you the help you need to lighten the load. Drawing on the wisdom of experts and parents alike, it provides practical tips and advice tailored to your unique challenges as a solo parent. Whether you're single, widowed, or have a partner who is unable to help, you'll discover how to do it all--with less stress. You'll learn to: Create a support system of family and friends Make time spent with your children more meaningful Shape a long-term career despite short-term demands Build a childcare backup bench Carve out time for yourself The HBR Working Parents Series provides support as you anticipate challenges, learn how to advocate for yourself more effectively, juggle your impossible schedule, and find fulfillment at home and at work. Whether you're up with a newborn or planning the future with your teen, you'll find the practical tips, strategies, and research you need to make working parenthood work for you.
Ch. 9: How to Negotiate Remote and Flexible Work Arrangements -- Ch. 10: Planning Your Career When Urgent Needs Get in the Way -- Ch. 11: Divorce Doesn't Have to Derail Your Career -- Ch. 12: How a Newly Widowed Mom of Three Kept Her Career on Track -- Section. 4: Tackle Stress with Self-Care -- Ch. 13: Combating Burnout as a Single Working Parent -- Ch. 14: Stress Can Be a Good Thing If You Know How to Use It -- Ch. 15: Make Time for "Me Time" -- Ch. 16: Resilience Is About How You Recharge -- Epilogue: You Live, You Learn -- Ch. 17: One Is Enough -- Notes -- About the Contributors -- Index
WorldCat record variable field(s) change: 050
Keywords: Single parents; Parenting; Single Parent; Parenting; Parents uniques; Rôle parental; Parenting; Single parents; elektronické knihy; electronic books